2016
DOI: 10.1097/igc.0000000000000639
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Incidental Fallopian Tube High-Grade Serous Carcinoma and Serous Tubal Intraepithelial Carcinoma in Women at Low Risk of Hereditary Breast and Ovarian Cancer

Abstract: Our study suggests that completion staging surgery for incidental STICs in non-BRCA patients may be considered. These patients should be offered hereditary testing. The Pelvic-Ovarian cancer INTerception (POINT) Project is an international registry set up to add to our understanding of STICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
(12 reference statements)
0
21
0
Order By: Relevance
“…It is apparent, the percentage of these women will have disseminated spread of high-grade serious cancer. Based on small series, authors have suggested comprehensive surgical staging including lymphadenectomy [23,24]. This is relatively a new condition with larger case series publication expected over the next few years.…”
Section: Early Stage Ovarian/tubal Cancermentioning
confidence: 99%
“…It is apparent, the percentage of these women will have disseminated spread of high-grade serious cancer. Based on small series, authors have suggested comprehensive surgical staging including lymphadenectomy [23,24]. This is relatively a new condition with larger case series publication expected over the next few years.…”
Section: Early Stage Ovarian/tubal Cancermentioning
confidence: 99%
“…Current evidence indicates the risk of subsequent ovarian HGSC is low (at least within the published follow-up periods), and it is unclear how to predict who will recur/progress. 8286 Using GEMMs, it is possible to test the effects of various genetic combinations (e.g. Trp53; Brca1; Pten vs. Trp53; Brca1; Rb1 ) on the response of mouse STICs to treatment (e.g.…”
Section: Specific Models and Prevention Studiesmentioning
confidence: 99%
“…The third patient had a colon adenocarcinoma and underwent hemicolectomy. No details of further follow-up were available [44].…”
Section: Stic Associated With Other Invasive Malignancies At Primary mentioning
confidence: 99%
“…A recent study from Chay et al published in 2016 reported the follow-up findings of a series of incidental fallopian tube high-grade serous carcinomas and STICs identified in women at low risk of hereditary breast and ovarian carcinoma, undergoing surgery for other indications [44]. Patients with known BRCA1 or BRCA2 mutations, or a family history of ovarian or breast carcinoma before the diagnosis of STIC or HGSC were excluded.…”
Section: Sticclinical Significance Of the Findingmentioning
confidence: 99%